Understanding Money - Reynolds, Eddie; Oldham, Matthew; Bryan, Lara; Bonatti, Marco (Illustrator) (Tulsa, Oklahoma : EDC Publishing, 2019)
"Some people say its not polite to talk about money. But if we dont talk about it, how will anyone understand how money works, what counts as fair pay, and why the rich are getting richer while the poor stay poor?"--Page 4 of cover.
Keywords: Money -- Juvenile literature; Saving and investment -- Juvenile literature; Finance, Personal -- Juvenile literature; Juvenile Non-fiction